2016
DOI: 10.4067/s0718-16202016000100005
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSES OF YOUNG Punica granatum PLANTS UNDER FOUR DIFFERENT WATER REGIMES

Abstract: . We evaluated the effect of the four treatments on canopy volume (CV) during two growing seasons. For 28 days during the second growing season, we evaluated soil moisture content (θ), the soil-moisture depletion factor (p), trunk cumulative growth (TCG), trunk growth rate (TGR) and maximum daily trunk shrinkage (MDS). We found relationships between CV and TCG and between CV and TGR. There were no differences in MDS among the irrigation treatments. We observed significant water stress in plants in the 0.3 ETc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
1
0
1
Order By: Relevance
“…Also, Wonderful variety was superior to Early 116 at all different irrigation levels (stress or non-stress treatments) in the two studied seasons. Similar results was found by Bugueño et al, (2016), they reported that canopy growth of pomegranate was at a maximum when soil watering was equivalent to 100% or 130% of evapotranspiration (Etc.). On the other hand, plants subjected to water deficits have been known to modify their patterns of water absorption, transpiration, enzyme activity and photosynthesis, interfering directly with the development of new shoots and canopy expression (Nortes et al, 2005).Reducing the number of new shoots could be a phenomenon by the plants to minimize the transpiration surface hence the water lost to the atmosphere, where water deficits decrease leaf growth by slowing rates of cell division and expansion due to turgor loss and increased synthesis of abscisic acid (Tezara et al, 2002).…”
Section: Number Of Sprouted Shootssupporting
confidence: 86%
“…Also, Wonderful variety was superior to Early 116 at all different irrigation levels (stress or non-stress treatments) in the two studied seasons. Similar results was found by Bugueño et al, (2016), they reported that canopy growth of pomegranate was at a maximum when soil watering was equivalent to 100% or 130% of evapotranspiration (Etc.). On the other hand, plants subjected to water deficits have been known to modify their patterns of water absorption, transpiration, enzyme activity and photosynthesis, interfering directly with the development of new shoots and canopy expression (Nortes et al, 2005).Reducing the number of new shoots could be a phenomenon by the plants to minimize the transpiration surface hence the water lost to the atmosphere, where water deficits decrease leaf growth by slowing rates of cell division and expansion due to turgor loss and increased synthesis of abscisic acid (Tezara et al, 2002).…”
Section: Number Of Sprouted Shootssupporting
confidence: 86%
“…La curva de TCP siempre se mantuvo por encima de la curva de TCR; el valor máximo durante todo el periodo de evaluación de TCP fue de 8316,3 μm, mientras que para TCR fue de 8265 μm. TCP es mayormente afectada por el proceso de rehidratación, que depende directamente del suministro de agua del suelo e indirectamente por la demanda de evaporación del día anterior, mientras que la alta sensibilidad de TCR puede ser uno de los primeros signos de estrés hídrico y pérdida de crecimiento del tronco (Bugueño et al, 2016). TCR puede ser usada como medida de crecimiento acumulado real durante una campaña, debido a que representa el crecimiento de masa de la planta; en cambio, TCP tiene mayor influencia del riego, temperatura y humedad (Figura 2).…”
Section: Tasa De Crecimiento Del Tronco Potencial Y Realunclassified
“…The reason for this is that this relationship depends on the phenological phase of the crop [ 13 , 20 ], pathogen incidence [ 21 ], water stress [ 15 ], or meteorological conditions [ 22 ]. Several studies have reported on intra- and interspecies lack of consistency of dendrometry data for pomegranate [ 16 , 23 ], table grapes [ 24 ], cherries [ 25 ], kaki [ 26 ], tomatoes [ 27 ], apples [ 17 ], lemon [ 28 ], olives [ 29 ], plums [ 16 ], and almonds [ 30 ], thus producing a wide diversity of models for each species. In addition, these previous studies showed that ~40% of stem diameter fluctuations were not related to the corresponding evapotranspiration, probably because the relationship might require nonlinear models or because these fluctuations are highly dependent on ETo intensity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%